Assessing arthritis in the context of cystic fibrosis. Issue 6 (5th March 2019) - Clarke, Elizabeth A.; Watson, Pippa; Freeston, Jane E.; Peckham, Daniel G.; Jones, Andrew M.; Horsley, Alex
Abstract: Inflammatory arthritis in the context of cystic fibrosis (CF) can represent a diagnostic and therapeutic challenge. Poor recognition and under‐treatment of musculoskeletal conditions increases symptom burden, affects quality of life, and may lead to changes to an individual's ability to carry out activities of daily living and to exercise. A careful assessment and multidisciplinary approach is essential when considering a diagnosis of CF‐associated arthritis (CFA), both in terms of identifying other treatable conditions, such as rheumatoid arthritis, and effectively addressing symptoms. In this collaboration between CF specialists and Rheumatologists, we consider joint symptoms in patients with CF, with a focus on CFA. We offer a differential diagnosis list and consider steps to assess and manage CF patients presenting with arthralgia including appropriate up‐to‐date rheumatological assessment.